2020
DOI: 10.1105/tpc.20.00111
|View full text |Cite
|
Sign up to set email alerts
|

Zipcode RNA-Binding Proteins and Membrane Trafficking Proteins Cooperate to Transport Glutelin mRNAs in Rice Endosperm

Abstract: In rice (Oryza sativa) endosperm cells, mRNAs encoding glutelin and prolamine are translated on distinct cortical-endoplasmic reticulum (ER) subdomains (the cisternal-ER and protein body (PB)-ER), a process that facilitates targeting of their proteins to different endomembrane compartments. Although the cis-and trans-factors responsible for mRNA localization have been defined over the years, how these mRNAs are transported to the cortical ER has yet to be resolved. Here, we show that the two interacting glutel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…In rice, RIP-seq was used to show that RNA-binding protein-P (RBP-P) is an RNA-binding protein that plays a role in endosomal trafficking of glutelin and prolamine mRNAs, working to anchor the RBP-bound mRNAs to the endosome via the quaternary complex and transport it to the ER Subdomain for translation, coopting endosomal trafficking [ 43 ] ( Table 2 ). RBP-L, an interacting partner of RBP-P, likely plays a coordinating role in subcellular trafficking of its mRNA targets, mediated by its 3’ UTR [ 44 ] ( Table 2 ).…”
Section: Overview Of Methods To Detect Rna-protein Interactions Anmentioning
confidence: 99%
“…In rice, RIP-seq was used to show that RNA-binding protein-P (RBP-P) is an RNA-binding protein that plays a role in endosomal trafficking of glutelin and prolamine mRNAs, working to anchor the RBP-bound mRNAs to the endosome via the quaternary complex and transport it to the ER Subdomain for translation, coopting endosomal trafficking [ 43 ] ( Table 2 ). RBP-L, an interacting partner of RBP-P, likely plays a coordinating role in subcellular trafficking of its mRNA targets, mediated by its 3’ UTR [ 44 ] ( Table 2 ).…”
Section: Overview Of Methods To Detect Rna-protein Interactions Anmentioning
confidence: 99%
“…The mRNP complex is formed at the cytoplasmic surface of early endosomes containing the glutelin cargo mRNA. Loss of function mutations in rab5a results in mistargeting of the mRNP complex verifying that endosomal transport of translationally inactive mRNAs is crucial for the efficient targeting of the mRNA to the cortical ER (Tian et al , 2020b ). This uncovers an alternative mode of mRNP attachment to endosomes via direct Rab5a interaction (Fig 2B ).…”
Section: Conservation and Biological Functions Of Endosomal Mrna Transportmentioning
confidence: 96%
“…Besides U . maydis , endosome‐mediated mRNA trafficking is also operational in other fungi (Müller et al , 2019 ; Stein et al , 2020 ), plants (Tian et al , 2020b ) and humans (Cioni et al , 2019 ; Liao et al , 2019 ). The phylogenetic analysis of the core endosomal mRNP transport machinery from U. maydis revealed that homologues of the components are present in other Basidiomycota.…”
Section: Conservation and Biological Functions Of Endosomal Mrna Transportmentioning
confidence: 99%
“…Emerging evidence from fungal model systems indicates that RBPs can directly function as membrane-bound proteins or interact with other membrane-associated linker proteins to link RNPs onto endosomes for the long-distance active transport of mRNAs (Jansen et al, 2014;Haag et al, 2015;Niessing et al, 2018). Indeed, a recent study indicated that RBPs associate with membrane trafficking proteins via intermediates to transport glutelin mRNAs in rice endosperm cells (Tian et al, 2020). Two interacting RBPs, RBP-P and RBP-L, form a quaternary complex with N-ETHYLMALEIMIDE-SENSITIVE FACTOR (NSF), a membrane fusion factor, and Rab5a, leading to glutelin mRNA transport on endosomes (Figure 1B).…”
Section: Mrna Localization and Metabolismmentioning
confidence: 99%
“…(i) How do different rice SSP mRNAs achieve localization in specific subregions of the ER? The paradigm that the fine-scale localization of glutelin mRNAs from the nucleus to a specific subregion of ER is mediated by endosomes via the association of RBPs with membrane trafficking proteins has been experimentally demonstrated (Tian et al, 2020). However, the localization of different SSP mRNAs seems to benefit from different combinations of RBPs and associated membrane trafficking proteins (Fukuda et al, 2016;Wang et al, 2016b;Chou et al, 2019b).…”
Section: Future Perspectivesmentioning
confidence: 99%